loyalty in the Holy Quran - Al-Hosan, Salama Awad (Journal of Islamic Sciences, 2021)
This study deals with the issue of loyalty in the Holy Quran. Because of its great importance in the Muslim faith and the impact it entails, and since this loyalty deals with many types, many people differed in its legitimacy, or expanded without restrictions, this study aimed to clarify the meaning and types of loyalty in the Holy Qur’an, and to know its most important aspects and the controls set by the Holy Quran for each of these types. To achieve these goals, the researcher followed: (the inductive approach) to collect and extrapolate the word loyalty in the Noble Qur’an, the (analytical) method to clarify the meaning of this word through its context in the Qur’an, and the (deductive) approach to derive the connotations of this word through the Qur’an context. And this study reached some results, the most important of which are: that loyalty may be to someone other than God in its worldly sense, and it may only be in its absolute meaning to God Almighty.